Determinants of consumers’ intention to use mobile commerce: DeLone and McLean perspective - Barry, Moussa; Haque, A. K. M. Ahasanul; Jan, Muhammad Tahir (IIUM Press, 2025)
ABSTRACT In the last few decades, substantial progress was seen in mobile commerce development. Although the Internet and smartphones have become more widely used in Malaysia, mobile commerce acceptance is still low. The current study investigates the determinants of intention to use mobile commerce among consumers in Malaysia. Additionally, this study aims at proposing a conceptual framework that emphasizes the impact of information quality, system quality, and service quality on consumer intentions to use mobile commerce in Malaysia. The DeLone and McLean Updated Information System Success Model (ISSM) Theory is the theoretical background of this study's proposed model. Mobile commerce providers must create user-friendly websites, applications, and platforms; they must also provide valuable information regarding their offerings, and provide high service quality to mobile commerce users to build a favourable intention to use mobile commerce in Malaysia. The primary contribution of this research is the conception of a model to examine the determinants of consumer intention to use mobile commerce in Malaysia. This research provides practical insights for mobile commerce service providers, enhancing their understanding of the determinants affecting consumer intention to use mobile commerce. This study will benefit academicians, scholars, students, providers, mobile marketing practitioners, and all industry stakeholders. Since this paper is conceptual, it necessitates empirical investigation to validate the proposed model of this study; thus, additional research is recommended.